Isolated trochlea osteochondral fracture of the distal humerus in a 6-year-old patient surgically fixed using biodegradable pins: A case study with over 3 years of follow-up. (August 2022) - Tsukamoto, Nobuaki; Mae, Takao; Hirabayashi, Kenichi; Matsushita, Yu; Baba, Satoshi; Komiya, Norihiro; Hayashida, Mitsumasa
Abstract: Isolated humeral trochlea fracture, particularly in skeletally immature children, is extremely rare. The exact mechanism of this injury remains unknown because the humeral trochlea is embraced within the olecranon fossa without any muscular or ligamentous attachment. We report the treatment of a 6-year-old boy who sustained an isolated trochlea osteochondral fracture when he fell with his elbow in a flexed position while skateboarding. The patient had a history of lateral condyle fracture of the ipsilateral humerus one year previously. At the diagnosis, computed tomography (CT) revealed a small bony fragment displaced anteromedially from the superior border of the trochlea with lifting of its lateral border. Ultrasonography confirmed instability of the fractured segment. At the time of surgery, the anterior trochlea surface fracture formed a hinged fracture line on its proximal and medial border. The fracture was anatomically reduced and fixed using biodegradable pins. Postoperatively, the involved elbow showed a sufficient functional recovery to a normal level without complications during 3 years of observation, although the biodegradable pins remained radiographically in place with partial degradation. The laterally opened avulsed fragment on primary CT clearly depicted the mechanism of injury: the impact entered from the lateral side of the elbow and progressed from the longitudinal ridge of the coronoid process onto the sulcus of the trochlea to shear off the anteromedial portion of the trochlea in a medial direction. The use of biodegradable pins for fixing a trochlea fracture in a skeletally immature patient provided favorable fracture healing; however, close observation is necessary until the completion of skeletal growth because of the lack of sufficient information on the long-term prognosis of trochlea fracture, especially when treated using biodegradable implants.